2016
DOI: 10.3928/1081597x-20151119-01
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Assisted LASIK Flap Complications

Abstract: The application of femtosecond laser technology to LASIK flap creation has increased greatly since its introduction. These lasers have improved the safety and predictability of the lamellar incision step. The majority of the femtosecond laser-assisted flap complications can be well managed without significant effects on refractive outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…In this study, we had neither free flaps, irregular flaps, decentered flaps, and epithelial defects, nor complications19 such as opaque bubble layer 20. In the IntraLase group, we had only one patient with transient light sensitivity syndrome21,22 and an eye with microstriae.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we had neither free flaps, irregular flaps, decentered flaps, and epithelial defects, nor complications19 such as opaque bubble layer 20. In the IntraLase group, we had only one patient with transient light sensitivity syndrome21,22 and an eye with microstriae.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Na et al [20] found that off-flap epipolis LASIK yielded superior visual recovery and corneal re-epithelialization than epipolis LASIK surgery in the early postoperative period. In addition, femto-LASIK surgery, despite allowing accurate, safe, and predictable in flap creation, occasionally involves either intraoperative or postoperative complications [21]. Hence, in the current study, we clinically compared the visual and refractive outcomes between femto-LASIK and flap-off epipolis LASIK surgery in myopia or myopic astigmatism; however, we found no statistically significant differences in these outcomes for two years between the groups.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, femto-LASIK surgery despite the accurate, safety, and predictable in flap creation, occasionally occur complications either intraoperatively or postoperatively. [19] Hence, in the current study, we clinically evaluated the visual and refractive outcomes between femto-LASIK and off-flap epi-LASIK surgery in myopia or myopic astigmatism, however, there were no statistically significant difference in refractive and visual outcomes between femto-LASIK and off-flap epi-LASIK surgery.…”
Section: Discussionmentioning
confidence: 85%